2007
DOI: 10.1097/wno.0b013e31814b1f66
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis for Central Retinal Artery Occlusion

Abstract: Central retinal artery occlusion (CRAO) frequently causes severe and irreversible visual loss. For many years, various conservative treatments have been proposed for acute CRAO, but their efficacy remains unproven. Over the past 20 years, CRAO has also been treated with thrombolytic agents administered intravenously or intra-arterially. However, all thrombolytic studies are retrospective and uncontrolled, so that the benefit of this treatment remains uncertain. A prospective controlled clinical trial is ongoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 53 publications
1
68
0
3
Order By: Relevance
“…In a summary of reported cases, Biousse et al found visual improvement in 48.5% of IV-treated and 34.9% of IA-treated patients, 2 which may be an improvement compared with the natural course. 2,8 A prospective randomized multicenter trial on intra-arterial tissue-type plasminogen activator was stopped because of lack of efficacy and a higher rate of adverse events. 4 A small randomized trial (n=16) on intravenous tissue-type plasminogen activator found improved visual acuity in 25% of patients, versus none after placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a summary of reported cases, Biousse et al found visual improvement in 48.5% of IV-treated and 34.9% of IA-treated patients, 2 which may be an improvement compared with the natural course. 2,8 A prospective randomized multicenter trial on intra-arterial tissue-type plasminogen activator was stopped because of lack of efficacy and a higher rate of adverse events. 4 A small randomized trial (n=16) on intravenous tissue-type plasminogen activator found improved visual acuity in 25% of patients, versus none after placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating intra-arterial or intravenous thrombolysis have yielded inconsistent results. [2][3][4] Ocular color-coded duplex sonography (OCCS) allows direct examination of the central retinal artery. Only few studies report on its value.…”
mentioning
confidence: 99%
“…[53][54][55] Its efficacy has been demonstrated in small retrospective studies. 19,44,53,[55][56][57][58][59] Several open-label observational trials have shown IA fibrinolysis to be effective in CRAO with up to 60-70% of treated subjects experiencing an improvement in VA. 39,53,56,58,60 A retrospective case-control study showed significantly that treatment with IA thrombolysis within 4 h resulted in better visual outcomes than in those treated later. 56 The Johns Hopkins Hospital looked at 42 CRAO patients between 1999 and 2006, with tPA delivered intraarterially in aliquots up to 15 h and noted a statistically significant improvement of three lines or more of vision improvement compared with control subjects who did not receive thrombolysis.…”
Section: Acute Management Of Craomentioning
confidence: 99%
“…44 Current literature suggests two main types of treatment for acute non-arteritic CRAO. The first is called 'standard' non-invasive measures and second is the use of thrombolytics, which can be deployed intravenously or intra-arterially.…”
Section: Acute Management Of Craomentioning
confidence: 99%
“…To this end, given the efficacy of intravenous rt-Pa for fibrinplatelet clot lysis in ischemic stroke and myocardial infarction, the role of systemic rt-Pa has also been explored for CRAO. 34 In a systematic review of 103 cases of acute CRAO, Biousse et al 9 reported a 48.5% improvement of at least 3 lines of visual acuity. Ultimately, given that the treatment window probably does not exceed 6-12 hours, developing quick transportation modalities for patients to emergency departments is essential.…”
Section: Future Directionsmentioning
confidence: 99%